Assessing the usability of the 2006 process evaluation of a grant-making organisation's enhancement of capacity programme - Bhikoo, Asgar (Institute for Monitoring and Evaluation, 2014)
Evaluations can only be effective if evaluators provide clients with improvements that are easy to understand, implement and fit their needs. Often evaluation recommendations are not used because these factors are overlooked once the evaluation has been completed. This evaluation assessed whether the client used the evaluation improvements recommended to them by evaluators. It presents a follow-up evaluation to a Process Evaluation conducted in 2006 on a Grant-making Organisation's Capacity Building Programme. It focuses on the Enhancement of Capacity Programme which is a core training programme within the Capacity Building Programme of the Grant-making Organisation. Furthermore this evaluation provides a programme description, a programme theory and a plausibility assessment of the programme theory.